The mechanism of flavonoids from Cyclocarya paliurus on inhibiting liver cancer based on in vitro experiments and network pharmacology - Mo, Jinggang; Tong, Yingpeng; Ma, Junxia; Wang, Kunpeng; Feng, Yifu; Wang, Liezhi; Jiang, Hao; Jin, Chong; Li, Junmin (Frontiers in Pharmacology, 2023)
Cyclocarya paliurus (Batal.) Iljinsk., a subtropical tree belonging to the family Juglandaceae, is rich in polysaccharides, flavonoids, and terpenoids. It has important pharmacological effects such as lowering blood lipids, blood sugar, and blood pressure. However, little has been discerned regarding anti-tumor effects and their potential mechanisms. In this study, in vitro experiments showed that an extract of C. paliurus total flavonoids significantly inhibited proliferation and promoted apoptosis in HepG2 cells. Previous work from our group applied HPLC-MS/MS to identify a total of 114 compounds in these CTF extracts, with 62 of these meeting Lipinski’s Rule of Five and containing targets in the Pubchem database. Network pharmacological analysis was applied to these 62 compounds and their targets, and 13 flavonoids were further screened for their potential anti-liver cancer activity. These 13 flavonoids included: tangeretin, baicalein, 7,4'-Dihydroxyflavone, velutin, 3-hydroxyflavone, chrysin, kumatakenin, tricin, luteolin, chrysoeriol, apigenin, pinocembrin, and butin. Together, these flavonoids were predicted to interact with AKT1, MAPK3, PIK3CA, EGFR, MAP2K1, SRC, IGF1R, IKBKB, MET, and MAPK14. It was predicted that the inhibitory effect on hepatocellular carcinoma would be accomplished by regulation of core proteins relating to such KEGG pathways as cancer (hsa05200), PI3K-Akt (hsa04151), Proteoglycans in cancer (hsa05205), microRNAs in cancer (hsa05206), and endocrine resistance (hsa01522) via core target proteins. Both 3-hydroxyflavone and luteolin were demonstrated to induce apoptosis and inhibit the proliferation of HepG2 cells. Our study provides scientific evidence supporting the use of CTFs for the treatment of liver cancer.